Analytical approach The problems faced by sociolinguistics - Kefaya Mathkoor shelsh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Language is the mirror of society, it reflects all its manifestations, from a civilization and paper, or backwardness and delay, it is clos ely related to all aspects of society. Therefore, language has received the attention of linguists, sociologists and anthropologists from the angle that it is a social phenomenon. Thus it has a science that examines linguistic issues and relations with society. This science is known as sociolinguistics. It studies the language in its relations with society, the social significance of all aspects of the structure of the language, and the methods of its use that are related to its social and cultural functions. In this paper I would like to treat some of Epistemological problematics in sociolinguistics concerning the sociological, and the sociolinguistic perspectives of social varieties.